Maqasid al-Shariah and Environmental Sustainability: An Islamic Economic Perspective - Klongrua, Silanee; Umuri, Khairil; Muftahuddin, Muftahuddin (Universitas Syiah Kuala, 2025)
This study explores the intersection of Maqasid al-Shariah (the objectives of Islamic law) and environmental sustainability, focusing on its implications within Islamic economics. Recognizing the increasing global challenges related to environmental degradation, this research highlights the essential role of Islamic principles in fostering sustainable economic practices. The Maqasid al-Shariah, which prioritize the preservation of life, intellect, lineage, wealth, and faith, inherently support environmental stewardship as a means to achieve balance and harmony. This study used a qualitative content analysis approach to investigate the integration of Maqasid al-Shariah and environmental sustainability in Islamic economics. Data was gathered from secondary sources, including peer-reviewed articles, policy documents, and reports from Islamic financial institutions. By examining Islamic teachings, ethical frameworks, and financial instruments such as green sukuk, the study demonstrates how Islamic economics can contribute to addressing environmental challenges. This work underscores the potential of faith-based economic systems to lead global efforts toward sustainability, advocating for a paradigm shift that integrates spirituality, ethics, and economic decision-making for the betterment of society and the planet.